2020
DOI: 10.3390/pathogens9090700
|View full text |Cite
|
Sign up to set email alerts
|

Short-Chain Fatty Acids Promote Mycobacterium avium subsp. hominissuis Growth in Nutrient-Limited Environments and Influence Susceptibility to Antibiotics

Abstract: Mycobacterium avium subsp. hominissuis (MAH) is a common intracellular pathogen that infects immunocompromised individuals and patients with pre-existing chronic lung diseases, such as cystic fibrosis, who develop chronic and persistent pulmonary infections. The metabolic remodeling of MAH in response to host environmental stresses or within biofilms formed in bronchial airways plays an important role in development of the persistence phenotype contributing to the pathogen’s tolerance to antibiotic treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 78 publications
1
11
0
Order By: Relevance
“…That finding agrees with the fact that the persistence state requires a suitable carbon and energy source (other than glucose) to maintain a low flux status through core metabolic pathways (Amato et al, 2014;Cabral et al, 2018). Furthermore, we have previously observed that the utilization of both short-chain fatty acid (SCFA) and glycerol by both planktonic and biofilm bacteria affects the susceptibility of M. avium to clinically used antibiotics in established biofilms (Silva et al, 2020). The results of the study demonstrate that glycerol and the SCFA are processed by M. avium in biofilms as an energy source, supporting M. avium growth in both biofilms but also in planktonic state (Silva et al, 2020).…”
Section: Figuresupporting
confidence: 83%
“…That finding agrees with the fact that the persistence state requires a suitable carbon and energy source (other than glucose) to maintain a low flux status through core metabolic pathways (Amato et al, 2014;Cabral et al, 2018). Furthermore, we have previously observed that the utilization of both short-chain fatty acid (SCFA) and glycerol by both planktonic and biofilm bacteria affects the susceptibility of M. avium to clinically used antibiotics in established biofilms (Silva et al, 2020). The results of the study demonstrate that glycerol and the SCFA are processed by M. avium in biofilms as an energy source, supporting M. avium growth in both biofilms but also in planktonic state (Silva et al, 2020).…”
Section: Figuresupporting
confidence: 83%
“…Strong support for propionic acid activating the Rcs system is its ability to activate three different Rcs-regulated promoters in the WT but not in an isogenic Rcs-deficient mutant. Due to its antimicrobial effects, propionic acid is commonly used as a food preservative ( 39 ) and topically to treat skin infections ( 56 ), and it may influence the susceptibility of bacteria to other antibiotics ( 57 , 58 ). However, the antimicrobial mechanism of action is not fully understood, and it has been hypothesized to be derived from intracellular acidification ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Strong support for propionic acid activating the Rcs system is its ability to activate three different Rcs-regulated promoters in the WT, but not an isogenic Rcs-deficient mutant. Due to its antimicrobial effects, propionic acid is commonly used as a food preservative (38), used topically to treat skin infections (51), and may affect antibiotic susceptibility (52, 53). However, the mechanism of action is not fully understood and is hypothesized to be derived from intracellular acidification (38).…”
Section: Discussionmentioning
confidence: 99%